APPLICATION OF MIND MAPPING WITH MULTIMEDIA IN IMPROVING NATURAL SCIENCE LEARNING OF THE FIFTH GRADE IN SDN 1 TAMANWINANGUN IN THE ACADEMIC YEAR OF 2014/2015. - Wahyuni, Gusti (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: Gusti Wahyuni. Application of Mind Mapping with Multimedia in Improving Natural Science Learning of The Fifth Grade in SDN 1 Tamanwinangun in the Academic Year of 2014/2015. The objectives of this research are: (1) to describe the steps in application of mind mapping with multimedia, (2) to improve Natural Science learning about simple plane of the fifth grade in SDN 1 Tamanwinangun. This research is a collaborative Class Action Research (CAR). The experiment was conducted in three cycles. Subjects were fifth grade students of SDN 1 Tamanwinangun in the academic year of 2014/2015, totaling 32 students. The results show that: (1) the application of mind mapping with multimedia has been carried out in accordance with the following steps: (a) introduction, (b) delivery, (c) deployment, (d) collaboration, (e) delivery of results, and (f) closure, (2) the application of mind mapping with multimedia can improve Natural Science learning about simple plane of the fifth grade in SDN 1 Tamanwinangun. Keyword:mind mapping, multimedia, learning, Natural Science Abstrak: Penerapan Mind Mapping dengan Multimedia dalam Peningkatan Pembelajaran IPA pada Siswa Kelas V SD. Tujuan penelitian ini yaitu: (1) mendeskripsikan penerapan mind mapping dengan multimedia, (2) meningkatkan pembelajaran IPA tentang pesawat sederhana pada siswa kelas V SDN 1 Tamanwinangun. Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam 3 siklus. Subjek penelitian adalah siswa kelas V SDN 1 Tamanwinangun berjumlah 32 siswa. Dari hasil penelitian disimpulkan bahwa: (1) penerapan mind mapping dengan multimedia dilaksanakan dengan langkah: (a) pendahuluan, (b) penyampaian, (c) penugasan, (d) kolaborasi, (e) penyampaian hasil, dan (f) penutup, (2) penerapan mind mapping dengan multimedia dapat meningkatkan pembelajaran IPA tentang pesawat sederhana pada siswa kelas V SDN 1 Tamanwinangun. Kata Kunci: mind mapping, multimedia, pembelajaran, IPA